If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6y = 69 Solving 2x + 6y = 69 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 2x + 6y + -6y = 69 + -6y Combine like terms: 6y + -6y = 0 2x + 0 = 69 + -6y 2x = 69 + -6y Divide each side by '2'. x = 34.5 + -3y Simplifying x = 34.5 + -3y
| 1-y^4=5y^2-35 | | .5(2y-15)+.6y=4.25 | | 21x+17=21x+17 | | 6n-7=29 | | .25x+1y+5z=100 | | 17y-y^2-5=-57+2y^2 | | ln(2+x^2)=0 | | ln(c^2+x^2)=0 | | 100+2x=4x | | 121a^2-49b^6= | | 18y-21=3y^2-24 | | 6b+2b=7 | | 16y-5=3y^2 | | 81Z^4-16=0 | | (y-8)*(y+8)= | | 12y^2=15y-3 | | 8-(6-2)=14 | | 12y^2=40y-3 | | 2y^2+128=40y^2 | | -48=-5+8-y | | x^4=3x^3+10x | | (X-1)=9-(y+2) | | (3x-5)(3x-5)=x+25 | | 3b+7=2+b | | 15x^2-44x= | | sqr(log(x))+1=0 | | 2*x^2-(5-i)*x+6=0 | | 3x^3*5x^2= | | 3x*5x^2= | | x*5x= | | 1.5(n-1)=n+3 | | 1.5n=n+4 |